2011
DOI: 10.1007/s10973-011-2057-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of hybrid materials based on epoxy functional (poly)siloxanes

Abstract: Epoxy functional (poly)siloxanes are one of the most important classes of modified silicones. Due to high reactivity of epoxy group and specific features of siloxane chain, they can make an excellent raw material for synthesis of hybrid materials. Results obtained in this study have shown that both the modification of epoxy resins with epoxy functional disiloxanes as well as the application of polysiloxanes with long polysiloxane chains and a specified content of epoxy groups makes it possible to produce hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The relative contributions to the overall reaction rate would be to make the effective activation energy dependent on the extent of oxidation. [19] In the current discussions, a step modeling method was adopted to extract the effective activation energy corresponding to the various oxidation stages.…”
Section: A Thermodynamic Aspectsmentioning
confidence: 99%
“…The relative contributions to the overall reaction rate would be to make the effective activation energy dependent on the extent of oxidation. [19] In the current discussions, a step modeling method was adopted to extract the effective activation energy corresponding to the various oxidation stages.…”
Section: A Thermodynamic Aspectsmentioning
confidence: 99%
“…By introducing the cationic photosensitive resin, the free-radical/cationic hybrid photosensitive resin can be prepared. 27 Cationic PIs are relatively insensitive to oxygen, which can initiate the polymerization of epoxy resin in oxygen-enriched environments, 28 and improve the curing rate as well as the storage performance of the hybrid resin.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid materials can be used in the textile, packaging, construction, automobile industries, as well as in micro-optics, microelectronics, in the synthesis of functional coatings or biosensors, biocatalysts, and novel materials for dentistry, cosmetics, therapeutic vectors, or biomedical purposes. [15][16][17] The literature offers numerous reports on modification of gelatin with silicon compounds; 18-21 however, there is little information about gelatin-siloxane systems obtained with organomodified silicones. However, a characteristic feature of this class of compounds is also their chemical inertness; therefore, to make reactive siloxanes, a modification of (poly)siloxane chains is performed by introducing various functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…The high reactivity of the oxirane ring of epoxides makes it possible to obtain a wide range of compounds or organic-inorganic hybrid materials. [15][16][17] The literature offers numerous reports on modification of gelatin with silicon compounds; [18][19][20][21] however, there is little information about gelatin-siloxane systems obtained with organomodified silicones. 19,22,23 Ren et al reported preparation of a new type of inorganic-organic hybrids based on gelatin and 3-(glycidoxypropyl)trimethoxysilane (GPTMS) through sol-gel processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation